(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the feasibility and effectiveness of Google Sites-Based Learning Media in the form of E-Books for the subject "Economic Activities" in Class 4 Elementary School Social Sciences. Furthermore, a validation test was carried out to ensure the usefulness and quality of Google Sites-based learning media for students at the fourth grade level in social studies. This research is development research that uses the ADDIE model which consists of five stages, namely, analysis, design, development, implementation and evaluation. As well as the research methods used through interviews, confirmation, observation, which are outlined in qualitative data analysis techniques in the form of reports to understand certain objects in the form of E-Books, which are collected through the results of this method. This is development research. This research intends to develop Web-based social studies teaching materials (Google Sites) for fourth grade students that focus on ’Economic Activities’ which will influence students to improve students’ critical thinking skills and digital literacy. Development of Google Sites-Based Learning Media in the form of E-Books accompanied by validation testing as well as analysis and mapping of test results.